Individual‐phase control of 3‐phase 4‐wire voltage–source converter. Issue 9 (1st September 2014) - Fazeli, Seyed Mahdi; Ping, Hew Wooi; Rahim, Nasrudin Bin Abd; Ooi, Boon Teck
Abstract : An innovative method of operating 3‐phase, 4‐wire voltage–source converters, based on decoupled P–Q control of individual phases, is presented. Individual‐phase control has six independent degrees of control freedom to deal with both symmetrical and asymmetrical operating conditions. Experimental tests on a laboratory distribution static synchronous compensator (D‐STATCOM) show that individual‐phase control can simultaneously (i) support the voltages of unbalanced 3‐phase loads against droop; (ii) equalise the complex powers at source‐side of the transmission line; (iii) balance the voltage magnitudes and (iv) balance the angles of 'ac' voltages at the point‐of‐common‐coupling.